The Davidic Messiah in the Old Testament Tracing a Theological Trajectory - Martin Daniel D. (Perichoresis: The Theological Journal of Emanuel University, 2022)
The present article revisits the issue of messianism, particularly as it finds its expression in the Davidic kingship tradition, that is, the belief concerning a Davidic Messiah. Since Old Testament messianic hope is inseparably associatied with the dynasty of David a study that traces the various perspectives concerning the Davidic Messiah chronologically and canonically can bring a contribution to this important Old Testament theme, too often neglected. Thus, the study shows that the belief in the coming of a Davidic Messiah is a prominent eschatological theme in the Old Testament. Its roots can be traced back to the historical covenant made by Yahweh with David, which receives hyperbolic and symbolical dimensions in the royal Psalms, and a full-fledged eschatological orientation in prophetic writings. The monarchic prophets: Isaiah, Micah, Amos, and Hosea draw on the covenant promises to David to ground their message regarding the coming of a ‘new David’, who would destroy the wicked, protect the poor and oppressed, and institute an eternal era of peace, justice, and righteousness. In the context of the Babylonian exile, Jeremiah and Ezekiel foresee that God will bring forth a righteous ‘shoot’ of Davidic line to reunite the nation and shepherd God’s people. In the post-exilic period, Zechariah underscores the promise that David’s son will build a house for Yahweh, moving from the initial historical focus on Zerubbabel and his role, to the eschatological expectation of the one and only messianic figure that will bring the final restoration.